2016
DOI: 10.1111/ipd.12261
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of endodontic treatments for immature necrotic permanent teeth based on clinical and radiographic outcomes: a systematic review and meta‐analysis

Abstract: Although almost all of the identified studies presented moderate risk of bias, MTA apexification seems to produce overall better clinical and radiographic success rates among the endodontic treatment available in immature necrotic permanent teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 37 publications
(95 reference statements)
0
49
0
1
Order By: Relevance
“…The use of RET has gained popularity with several published case reports/series (Kontakiotis et al 2015), a growing base of randomized controlled trials (Nagata et al 2014, Nagy et al 2014, Bezgin et al 2015, several systematic reviews (Moreno-Hidalgo et al 2013, Kontakiotis et al 2014) and a meta-analysis (Nicoloso et al 2016). Despite agreeing that the success of this technique in achieving regeneration rather than revascularization/repair/mutagenesis is dependent upon achieving four essential tissue engineering principles mainly (i) availability of suitable stem cells, (ii) a scaffold for the stem cells to populate and orient in three dimensional manner, (iii) appropriate signalling molecules promoting stem cell differentiation into the desired odontoblasts and (iv) disinfection of the root canal system without damage to stem cells (Wigler et al 2013, Galler 2015, several RET techniques have been used and reported (Kontakiotis et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of RET has gained popularity with several published case reports/series (Kontakiotis et al 2015), a growing base of randomized controlled trials (Nagata et al 2014, Nagy et al 2014, Bezgin et al 2015, several systematic reviews (Moreno-Hidalgo et al 2013, Kontakiotis et al 2014) and a meta-analysis (Nicoloso et al 2016). Despite agreeing that the success of this technique in achieving regeneration rather than revascularization/repair/mutagenesis is dependent upon achieving four essential tissue engineering principles mainly (i) availability of suitable stem cells, (ii) a scaffold for the stem cells to populate and orient in three dimensional manner, (iii) appropriate signalling molecules promoting stem cell differentiation into the desired odontoblasts and (iv) disinfection of the root canal system without damage to stem cells (Wigler et al 2013, Galler 2015, several RET techniques have been used and reported (Kontakiotis et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Kontakiotis et al 2015), a growing base of randomized controlled trials(Nagata et al 2014, Nagy et al 2014, Bezgin et al 2015, several systematic reviews(Moreno-Hidalgo et al 2013, Kontakiotis et al 2014) and a meta-analysis(Nicoloso et al 2016)…”
mentioning
confidence: 99%
“…Albeit inconsistent, the ability of this technique to promote root lengthening, thickening of root dentinal walls and apical closure (Table 1; Nicoloso et al . 2016, Tong et al . 2017, Torabinejad et al .…”
Section: Introductionmentioning
confidence: 99%
“…Dental tissue regeneration has recently emerged as an exciting new concept in managing immature teeth with nonvital pulps (European Society of Endodontology 2016) with several published protocols having variable outcomes (Nicoloso et al 2017). These protocols share common steps involving chemical disinfection, utilization of stem cells of the apical papilla and scaffold creation through induction of a blood clot (Galler 2016).…”
Section: Introductionmentioning
confidence: 99%